Pathogens crossing borders: global animal diseases and international responses, 1860-1947 - Knab, Cornelia (Routledge studies in the history of science, technology and medicine, 2022)
"The increasing globalization of trade, travel and transport since the mid-19th century had unwelcome consequences - one of them was the spread of contagious animal diseases over greater distances in a shorter time than ever before. Borders and national control strategies proved to be insufficient to stop the pathogens. Not surprisingly, the issue of epizootics (epidemics of animals) was among the first topics to be addressed by international meetings from the 1860s onwards. Pathogens Crossing Borders explores the history of international efforts to contain and prevent the spread of animal diseases from the early 1860s to the years after the Second World War. As an innovative contribution to global history and the history of internationalism, the book investigates how disease experts, politicians and state authorities developed concepts, practices and institutional structures at the international level to tackle the spread of animal diseases across borders. By following their activities in dealing with a problem area which was - and is today - of enormous political, social, public health and economic relevance, the book reveals the historical challenges of finding common international responses to complex and pressing global issues for which there are no easy solutions"--
Eingereicht unter dem Titel: 'Organizing Trust': International Cooperation against Animal Diseases, 1863-1946
Includes bibliographical references and index
Keywords: Geschichte 1860-1947; Hochschulschrift; Epidemiologie; Tiergesundheit